Design and implementation of HDL remote controller for smart home system - I. H. Hamzah; M. S. Z. Suhaimi; A. A. Malik; A. F. A. Rahim (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This work presents a design and development of a remote controller application using an Altera DE2-115 board. A remote controller lighting provides smart technologies make it viable to monitor, control and support users in which can enhance the quality life and promote independent living. Nowadays, to turn on the electrical devices, a user will go to the located switch. It is difficult and required more time to switch on the devices instead of staying at certain location while controlling the switching mode of the devices. Implementing this system, users do not need to have numerous switches in their home to turn on the lights as they can do this digitally from a switchless control located in one place or using a remote controller. The Altera board is built with eighteen slide switches which act as inputs and at the same time it will display the outputs on seven segments, LEDs and LCD display character. As a conclusion, the remote controller lighting system provides convenience and energy efficiency in order to allow the users to control the lighting system using smart devices.